PROMs in post-mastectomy care: Patient self-reports (BREAST-Q™) as a powerful instrument to personalize medical services. Issue 6 (June 2020) - Ghilli, M.; Mariniello, M.D.; Camilleri, V.; Murante, A.M.; Ferrè, F.; Colizzi, L.; Gennaro, M.; Caligo, M.A.; Scatena, C.; Del Re, M.; Nuti, S.; Caramella, D.; et al.
Abstract: One of the goals of immediate breast reconstruction (IBR) is to satisfy the patient's outcome. Recent studies therefore tended to focus on the patient's perception of the care and on the impact on quality of life using patients-reported-outcome-measures (PROMs), able to measure the health status directly without the clinician's interposition. We present a preliminary prospective study on 333 patients who underwent mastectomy with IBR in a two-year period, in a single Italian centre, using a dedicated PROMs, the BREAST-Q™, to determine the patient's satisfaction. We studied two groups of IBR: Group A (two-step with tissue-expander) and Group B (one-step: prosthesis/mesh) and conducted a pre- and post-operative comparison for each group to evaluate score-gain over time, and a group-score comparison to determine whether differences were significant between reconstruction types. Two-hundred-and-nine were actually enrolled and 132 completed all the questionnaires. The response rate was 62.8% and the compliance rate (completion of all the questionnaires) was 63.1%. In both groups all the analyzed domains worsened comparing the pre and post-operative period; the differences were statistically significant only for physical and sexual-wellbeing. In the comparison between the two groups, none of the detected differences reached the statistical significance. According to our experience, we can state that PROMs could improve the health concept redefining the variables to be monitored even if data is still insufficient to draw any definitive conclusion. PROMs can help surgeons and patients decide the most appropriate surgery for a particular patient-profile and to identify those who require further support.